The Multimodal Go-Nogo Simon Effect: Signifying the Relevance of Stimulus Features in the Go-Nogo Simon Paradigm Impacts Event Representations and Task Performance - Dolk, Thomas; Liepelt, Roman (Frontiers in Psychology, 2018)
Numerous studies have shown that stimulus-response-compatibility (SRC) effects in the go-nogo version of the Simon task can be elicited as a result of performing the task together with another human or non-human agent (e.g., a Japanese-waving-cat, a working-clock, or a ticking-metronome). A parsimonious explanation for both social and non-social SRC effects is that highlighting the spatial significance of alternative (non-/social) action events makes action selection more difficult. This holds even when action events are task-irrelevant. Recent findings, however, suggest that this explanation holds only for cases of a modality correspondence between the Simon task as such (i.e., auditory or visual) and the alternative (non-/social) action event that needs to be discriminated. However, based on the fact that perception and action are represented by the same kind of codes, an event that makes the go-nogo decision more challenging should impact go-nogo Simon task performance. To tackle this issue, the present study tested if alternative stimulus events that come from a different sensory modality do impact SRC effects in the go-nogo version of the Simon task. This was tested in the presence and absence of alternative action events of a human co-actor. In a multimodal (auditory–visual) go-nogo Simon paradigm, participants responded to their assigned stimulus – e.g., a single auditory stimulus while ignoring the alternative visual stimulus or vice versa – in the presence or absence of a human co-actor (i.e., joint and single go-nogo condition). Results showed reliable SRCs in both, single and joint go-nogo Simon task conditions independent of the modality participants had to respond to. Although a correspondence between stimulus material and attention-grabbing event might be an efficient condition for SRCs to emerge, the driving force underlying the emergence of SRCs rather appears to be whether the attentional focus prevents or facilitates alternative events to be integrated. Thus, under task conditions in which the attentional focus is sufficiently broad to enable the integration and thus cognitive representation of alternative events, go-nogo decisions become more difficult, resulting in reliable SRCs in single and joint go-nogo Simon tasks.